Performance Evaluation and Model of GFRP Reinforced Concrete Filled GFRP Tube Column under Accelerated Aging - Prachasaree, Woraphot; Ouiseng, Jakrawa; Hawa, Abideng; Intarit, Pong-in; Wangapisit, Ornkamon; Limkatanyu, Suchart (Civil Engineering Journal, 2026)
Conventional reinforced concrete structures exposed to aggressive environments show a risky tendency toward performance degradation due to concrete deterioration and reinforcement corrosion. Consequently, the use of fiber-reinforced polymer (FRP) materials in concrete structures as one of the alternative potential materials for mitigating serious durability issues in structural applications has gained increasing acceptance. The study aims to evaluate the performance and durability of GFRP-reinforced concrete-filled GFRP tube columns under accelerated aging. Three different column specimens, 1) GFRC-F-GFT, 2) GFRC, and 3) C-F-GFT, were immersed under water at 80°C for 12 hrs (wet phase), followed by specimen placement above water at ambient room temperature for 12 hrs (dry phase) in each aging cycle. The behavior and performance of the specimens were experimentally investigated through uniaxial compressive loading. The experimental results were evaluated to develop a strength capacity model that incorporated the environmental exposure effect through the strength reduction factors (C0, h1, and h2). To establish the correlation between accelerated and natural aging, field investigation data under the tropical marine environment and the simplified time-invariant model were utilized to predict structural performance. Based on this study, the GFRC-F-GFT specimen degradation under accelerated wet-dry aging at 290 cycles can reduce axial column capacity up to 50%, which is equivalent to the predicted degradation under a natural tropical marine environment over 50 years.